ANALISIS KETIMPANGAN PENDAPATAN PERKAPITA DI SUMATERA: PENDEKATAN REGRESI DEKOMPOSISI - Yazid Al Rusydi, Naufal; Yuliawan, Dedy (Berajah Journal, 2024)
Income inequality occurs across all regions of Indonesia, both in urban and rural areas. This phenomenon exacerbates poverty, making the poor even poorer. This study focuses on the island of Sumatra, which still has many underdeveloped regions. The method used in this research is Decomposition Regression, aiming to prove whether there is indeed per capita income inequality in Sumatra. The data analyzed includes various economic indicators from all provinces in Sumatra, including Gross Regional Domestic Product (GRDP) and income distribution. The research results show significant per capita income inequality in Sumatra. This inequality is primarily caused by substantial differences in GRDP between urban and rural areas as well as between cities and regencies. The study found that regions with high GRDP tend to experience faster welfare improvement compared to regions with low GRDP. These findings indicate the need for more equitable economic policies to reduce income inequality and improve welfare throughout Sumatra. The study also highlights the importance of investing in infrastructure and education in underdeveloped areas to support more inclusive and sustainable economic growth. This research underscores the critical need for targeted development efforts to bridge the economic gap and promote balanced regional development.